Rebecca - Du Maurier, Daphne, 1907-1989. (London : Orion Books, 2007)
The second Mrs. Maxim de Winter finds it difficult and frightening to live in the shadow of her predecessor, a situation that is exacerbated by her husband's moodiness, and the presence of sinister housekeeper, Mrs. Danvers.
Adult.
Adult
Keywords: Country homes -- England -- Cornwall (County) -- Fiction; Man-woman relationships -- Fiction; Love stories; Man-woman relationship -- Fiction; Romantic suspense novels; Cornwall (England : County) -- Fiction; Cornwall (England : County) -- Fiction; Romantic suspense novels